1974
DOI: 10.1099/0022-1317-22-1-81
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Three Functional RNA Species in several Strains of Cucumber Mosaic Virus

Abstract: SUMMARYThe RNA content of four different CMV strains was investigated. All RNA preparations always contained the four major RNA species described by Kaper & West (I972), while most preparations also contained several minor RNA species. The four largest RNAs were separated by sucrose density-gradient centrifuging and by electrophoresis on polyacrylamide gels. Combination experiments suggest, for all strains, that the genome consists of the three largest RNAs (1 + 2 + 3), while RNA 4 is not required for infectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(11 citation statements)
references
References 17 publications
(1 reference statement)
0
11
0
Order By: Relevance
“…Although no direct investigation has addressed this question, some data indicating unequal accumulation of different genome segments can be found, for example, in studies on cucumber mosaic virus [38][39][40][41] , tomato aspermy virus 42,43 and brome mosaic virus 44 -all positive-sense ssRNA viruses unrelated to FBNSV. These earlier studies were either purely descriptive, analysing the physical and/or chemical properties of the virus particle 38,39,42,44 , or focused on technical developments for RNA quantification 40,41,44 . Nevertheless, they suggest that the regulation of segment copy number may be a general feature of multipartite viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Although no direct investigation has addressed this question, some data indicating unequal accumulation of different genome segments can be found, for example, in studies on cucumber mosaic virus [38][39][40][41] , tomato aspermy virus 42,43 and brome mosaic virus 44 -all positive-sense ssRNA viruses unrelated to FBNSV. These earlier studies were either purely descriptive, analysing the physical and/or chemical properties of the virus particle 38,39,42,44 , or focused on technical developments for RNA quantification 40,41,44 . Nevertheless, they suggest that the regulation of segment copy number may be a general feature of multipartite viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Cucumber mosaic virus (CMV) is a positive-sense RNA plant virus with a tripartite genome consisting of single-stranded RNAs, designated RNA1, 2 and 3 in decreasing order of molecular weight (Mr) 13,18). In the course of our study on molecular aspects of CMV, we have already made cDNA clones and reported the complete nucleotide sequences of RNA316) and RNA212) of Japanese Y strain of CMV (CMV-Y)25).…”
Section: Introductionmentioning
confidence: 99%
“…Cucumber mosaic virus (CMV) contains a functionally divided RNA genome (Peden & Symons, 1973;Lot et al, 1974). The three single-stranded positive-sense RNA segments, RNA-1, -2 and -3 have mol.…”
Section: Introductionmentioning
confidence: 99%